Method for preparing proton exchange membrane through response surface optimization

The process parameters of the proton exchange membrane are regulated through the response surface optimization method, which solves the problem of difficult film thickness, achieves the high proton conductivity and stability of the proton exchange membrane, and improves the overall performance of the fuel cell.

CN119481186APending Publication Date: 2025-02-18江苏深储新材料有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411510226.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the thickness of the proton exchange membrane, thereby affecting its performance, especially its proton conductivity and stability.

Method used

The response surface optimization method is adopted to prepare an optimized proton exchange membrane by adjusting the process parameters such as the mass fraction, pulling speed and drying temperature of the cast film liquid. Specific steps include single-factor tests and response surface optimization, and establishing a regression model to guide the optimal preparation process of the membrane.

Benefits of technology

It realizes precise control of the thickness of the proton exchange membrane, improves the proton conductivity and stability of the membrane, and provides more efficient fuel cell performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481186A_ABST
    Figure CN119481186A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of proton exchange membrane preparation methods, and relates to a method for preparing a proton exchange membrane through response surface optimization. According to the method, a single-factor extraction test is carried out by taking the mass fraction of a membrane casting solution containing liquid crystal performance, the pulling speed and the drying temperature as influence factors, the influence of the mass fraction of the membrane casting solution containing liquid crystal performance, the pulling speed and the drying temperature on the membrane thickness of the proton exchange membrane is determined, and a response surface method test is designed; the optimal process conditions for preparing the proton exchange membrane are determined as follows: the mass fraction of the membrane casting solution containing the liquid crystal performance is 2.08%, the pulling speed is 82.23 mm / min, the drying temperature is 60.30 DEG C, and the actual measured average value of the thickness of the proton exchange membrane obtained under the conditions for three times is 33 + / -1 [mu] m. The prepared proton exchange membrane has high proton conductivity, and the method is provided for improving the proton conductivity of the proton exchange membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of proton exchange membrane preparation methods, and in particular relates to a method for preparing a proton exchange membrane by response surface optimization. Background Art

[0002] Proton exchange membrane fuel cell is an efficient and clean energy conversion device, and its core component is the proton exchange membrane. The proton exchange membrane not only separates the fuel and oxidant, but also conducts protons; therefore, its performance directly affects the overall efficiency and life of the fuel cell. With the continuous development of fuel cell technology, the performance requirements for proton exchange membranes are becoming higher and higher, including high proton conductivity, good chemical stability, dimensional stability, thermal stability, and mechanical properties.

[0003] At present, polytetrafluoroethylene (PTFE) is a polymer material with excellent performance. Its molecular structure is composed of CF bonds and has extremely high bond energy, so it has extremely high chemical stability and thermal stability. Sulfonated polyetheretherketone (SPEEK) has excellent proton conductivity. The high chemical stability and thermal stability of PTFE combined with the proton conductivity of SPEEK can be used to prepare proton exchange membranes with excellent performance. However, the water absorption rate and swelling rate increase with the increase of sulfonation degree, which is not conducive to the stability of the proton exchange membrane.

[0004] The thickness of the proton exchange membrane is inversely proportional to the proton conductivity, so preparing a thinner proton exchange membrane is more conducive to proton transport. The commonly used preparation method is solution casting, but this method is to cast the polymer solution directly into a flat mold, and then wait for the solvent to evaporate and form a membrane at an appropriate temperature, so the membrane is usually thicker. Compared with the solution casting method, the proton exchange membrane prepared by the pull-up coating method is usually thinner. This is because the pull-up coating method immerses the substrate in a solution containing the polymer and then slowly pulls it out, so that the solution forms a thin film on the substrate. By regulating its process parameters (such as pulling speed and drying temperature), the thickness of the membrane can be precisely controlled, and a thinner proton exchange membrane can be prepared. At present, there is little research on regulating the thickness of proton exchange membranes to improve their performance.

[0005] Therefore, it is particularly important to provide a method for optimizing multiple factors to optimize the thickness of the proton exchange membrane, develop new proton exchange membranes, and provide a reference basis for the development and utilization of proton exchange membranes. Summary of the invention

[0006] In view of the above technical problems, the present invention provides a method for preparing proton exchange membranes by response surface optimization. The present invention obtains the best process for preparing proton exchange membranes, and the established regression model can be used to guide the preparation of proton exchange membranes, which is beneficial to the subsequent research on proton exchange membranes.

[0007] To achieve the above-mentioned purpose, the present invention adopts the following technical solutions.

[0008] A method for preparing a proton exchange membrane by response surface optimization specifically comprises the following steps:

[0009] Step 1, immersing a glass sheet with polytetrafluoroethylene (PTFE) as a matrix in a sulfonated polyetheretherketone casting solution (LCSC) containing liquid crystal properties, and then pulling the PTFE matrix upward to obtain a PTFE matrix coated with the casting solution;

[0010] Step 2, taking the mass fraction of the casting solution, the pulling speed and the drying temperature as the influencing factors, performing multiple single factor extraction tests on the proton exchange membrane, taking the membrane thickness as the judgment standard, and obtaining the influence of each factor on the membrane thickness of the proton exchange membrane according to the single factor test;

[0011] Step 3, using the response surface method to optimize the three variable parameters of the casting solution mass fraction, the pulling speed and the drying temperature, and obtaining the regression equation with the film thickness as the response value;

[0012] Step 4: According to the quadratic regression model equation, the condition corresponding to the minimum value of the membrane thickness under the interaction of the factors under consideration is determined as the optimal production process parameter of the proton exchange membrane;

[0013] Step 5: Prepare a proton exchange membrane according to the optimal production process parameters of step 4.

[0014] Furthermore, in step 1, the preparation method of the glass sheet with polytetrafluoroethylene (PTFE) as the matrix is: soak the polytetrafluoroethylene membrane in anhydrous ethanol, ultrasonically clean it for 30 minutes and then dry it at 100°C to obtain a treated PTFE membrane, and stick the treated PTFE membrane to a clean glass sheet to obtain a glass sheet with polytetrafluoroethylene (PTFE) as the matrix.

[0015] Furthermore, in step 1, the preparation method of the sulfonated polyetheretherketone casting solution (LCSC) containing liquid crystal properties is: the polyetheretherketone proton exchange membrane casting solution containing sulfonic acid side chains and the meta-aramid fiber containing liquid crystal properties are mixed and stirred at 60° C. for 3 hours to obtain a casting solution containing 1%-5% of the meta-aramid fiber containing liquid crystal properties by mass; the casting solution is named LCSC.

[0016] Furthermore, in step 2, the mass fraction of the casting solution is 1%-5%, the pulling speed is 20-100 mm / min, and the drying temperature is 40-80°C.

[0017] Furthermore, in step 3, the mass fraction of the casting solution is 1%-3%, the pulling speed is 60-100 mm / min, and the drying temperature is 50-70°C.

[0018] Furthermore, in step 3, the regression equation is:

[0019] d=35.19-0.75A-0.34B-0.11C-0.38AB+0.29AC-0.61BC+4.85A 2 +1.72B 2 +2.61C 2 .

[0020] Wherein, the response value d is the film thickness, in μm; A is the mass fraction, i.e. the mass fraction of the casting liquid, in %; B is the pulling speed, in mm / min; C is the drying temperature, in ℃.

[0021] Furthermore, in step 4, the optimal production process parameters are: the mass fraction of the casting liquid is 2.08%, the pulling speed is 82.23 mm / min, and the drying temperature is 60.30°C.

[0022] Furthermore, in step 4, the minimum value of the film thickness is 33±1 μm.

[0023] Furthermore, the structure of the polyetheretherketone proton exchange membrane casting solution containing sulfonic acid side chains is as follows:

[0024]

[0025] Furthermore, the structure of the meta-aramid fiber containing liquid crystal properties is as follows:

[0026]

[0027] Compared with the prior art, the present invention has the following beneficial effects.

[0028] 1. Polytetrafluoroethylene (PTFE) is a polymer material with excellent performance. Its molecular structure is composed of CF bonds and has extremely high bond energy, so it has extremely high chemical stability and thermal stability. The side chains of the proton conductor groups in the sulfonated polyetheretherketone casting solution (LCSC) with liquid crystal properties form a hydrogen bond network, and the molecules are arranged in an orderly manner within the liquid crystal phase, which can form an orderly proton transmission channel and effectively promote proton conduction. The high chemical stability and thermal stability of PTFE combined with the proton conduction performance of LCSC can be used to prepare proton exchange membranes with excellent performance.

[0029] 2. The present invention uses the mass fraction of the casting liquid containing liquid crystal properties (i.e. the mass fraction of the casting liquid), the pulling speed and the drying temperature as the influencing factors to carry out multiple single factor extraction tests on the thickness of the proton exchange membrane, and determines that the mass fraction of the casting liquid containing liquid crystal properties, the pulling speed and the drying temperature have an influence on the thickness of the proton exchange membrane. On the basis of the single factor test, a three-factor three-level response surface method test is designed, and the optimal process parameters for preparing the proton exchange membrane are finally determined, the mass fraction of the casting liquid containing liquid crystal properties is 2.08%, the pulling speed is 82.23mm / min, and the drying temperature is 60.30℃. Under these conditions, three parallel experiments are carried out, and the average value of the proton exchange membrane thickness is obtained to be 33±1μm, which is less different from the predicted value of 33μm, and the error is within 1%, indicating that the model established by the single factor method and the response surface method is effective and feasible, and can be used to guide the preparation of the proton exchange membrane. By optimizing the preparation process, the membrane of the present invention performs well in proton conductivity, which is beneficial to the subsequent research of the proton exchange membrane and provides a reference basis for the development and utilization of the proton exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of preparing proton exchange membrane by the pulling coating method.

[0031] Figure 2 This is a polarizing microscope image showing the effect of mass fraction on the morphology of sulfonated polyetheretherketone casting solution containing liquid crystal properties.

[0032] Figure 3 This is a schematic diagram of the effect of pulling rate on the thickness of proton exchange membrane.

[0033] Figure 4 This is a schematic diagram showing the effect of drying temperature on the thickness of the proton exchange membrane.

[0034] Figure 5 These are the response surface diagram and contour diagram of the effects of casting solution mass fraction and pulling speed on proton exchange membrane thickness.

[0035] Figure 6 These are the response surface diagram and contour diagram of the effects of casting solution mass fraction and drying temperature on proton exchange membrane thickness.

[0036] Figure 7 These are the response surface diagram and contour diagram of the effects of pulling speed and drying temperature on the thickness of the proton exchange membrane.

[0037] Figure 8 It is a comparison chart of the proton conductivity of the proton exchange membranes prepared in Example 1 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with examples, but the implementation mode of the present invention is not limited to the scope represented by the examples.

[0039] The test methods involved in the embodiments and comparative examples are as follows:

[0040] Morphology analysis: performed using a Zeiss polarizing microscope.

[0041] Proton conductivity test: completed by Shanghai Chenhua CHI660C electrochemical workstation, using a two-electrode test method, in accordance with GB / T 20042.3-2022 test, the data collection method is electrochemical impedance spectroscopy, the constant voltage is 5mV, and the test frequency range is from 1Hz to 100kHz. Proton conductivity can be calculated by the following formula:

[0042]

[0043] Wherein, σ (S / cm) represents proton conductivity, L (cm) represents the internal distance between two stainless steel electrodes, d (cm) represents the width of the membrane, h (cm) represents the thickness of the membrane, and R (Ω) represents the impedance value of the membrane, which is taken from the intersection of the diffusion-controlled straight line and the X-axis in the electrochemical impedance spectroscopy.

[0044] Example 1.

[0045] A method for preparing a proton exchange membrane by response surface optimization specifically comprises the following steps:

[0046] 1. Sample Preparation

[0047] (1) Pretreatment of polytetrafluoroethylene (PTFE) membrane: a 5*2 cm polytetrafluoroethylene membrane was immersed in anhydrous ethanol, ultrasonically cleaned for 30 minutes, and then dried at 100°C. The treated PTFE membrane was pasted onto a clean glass sheet to obtain a glass sheet with PTFE as the matrix.

[0048] (2) Preparation of sulfonated polyetheretherketone casting solution (LCSC) with liquid crystal properties: 0.0378 g, 0.2643 g, 0.4967 g, 0.7322 g and 0.974 g of meta-aramid fiber with liquid crystal properties were slowly added into five 19 ml polyetheretherketone casting solutions containing sulfonic acid side chains, respectively. The mixture was stirred at 60 °C for 3 h to obtain five sulfonated polyetheretherketone casting solutions with different mass fractions of liquid crystal properties.

[0049] (3) Preparation of LCSC / PTFE membrane: A glass sheet with PTFE as the matrix is ​​immersed in the LCSC casting solution, and then the PTFE matrix is ​​pulled upward to obtain a PTFE matrix coated with the casting solution, such as Figure 1 shown.

[0050] 2. Single Factor Experiment

[0051] Taking the thickness of proton exchange membrane (d) as the evaluation index, the effects of three factors, namely the mass fraction of casting solution containing liquid crystal properties (i.e. mass fraction), pulling speed and drying temperature on the performance of proton exchange membrane, were investigated.

[0052] (1) Under the conditions of pulling speed of 80 mm / min and drying temperature of 60°C, the effects of mass fraction (1%, 2%, 3%, 4% and 5%) on the properties of PEM liquid crystal were investigated. The results are as follows Figure 2 shown.

[0053] (2) Under the conditions of 2% mass fraction and drying temperature of 60°C, the effect of pulling speed (20, 40, 60, 80, 100 mm / min) on the thickness of proton exchange membrane was investigated. The results are as follows: Figure 3 shown.

[0054] (3) Under the conditions of 2% mass fraction and pulling speed of 80 mm / min, the effect of drying temperature (40, 50, 60, 70, 80°C) on the thickness of proton exchange membrane was investigated. The results are as follows: Figure 4 shown.

[0055] 3. Response surface optimization experiment

[0056] On the basis of single factor experiment, three factors including mass fraction (A), pulling speed (B) and drying temperature (C) were selected as independent variables, and the thickness of proton exchange membrane (d) was used as the evaluation index. The Box-Behnken (BBD) response surface design with three factors and three levels was used to optimize the preparation process of proton exchange membrane. The factors and levels of the response surface experiment are shown in Table 1.

[0057] Table 1 Effect of three factors and horizontal orthogonal test on the pulling coating process

[0058]

[0059] 4. Proton conductivity test

[0060] The proton exchange membrane prepared with the best process parameters from the response surface optimization experiment was immersed in deionized water at 80°C, and the proton conductivity at different temperatures was tested.

[0061] 5. Results and Analysis

[0062] 5.1 Single factor experiment for optimization of proton exchange membrane preparation process

[0063] 5.1.1 Effect of the mass fraction of the casting solution containing liquid crystal properties on the liquid crystal properties of proton exchange membranes

[0064] Depend on Figure 1It can be seen that when the mass fraction of the casting liquid is 1% and 2%, a characteristic fan-shaped texture appears in the LCSC composite material, and a finger-shaped texture appears at 3%, which are all morphological manifestations of the liquid crystal phase range. However, when the mass fraction is 4% and 5%, the birefringence disappears and no liquid crystal characteristics appear. Taking all factors into consideration, it is more appropriate to select a casting liquid with a mass fraction of 1%, 2% and 3% containing liquid crystal properties.

[0065] 5.1.2 Effect of pulling speed on proton exchange membrane thickness

[0066] Depend on Figure 2 It can be seen that with the increase of pulling speed, the thickness of the proton exchange membrane shows a trend of first decreasing and then increasing. When the pulling speed is 80mm / min, the minimum thickness of the proton exchange membrane is 35±1μm. This is because when the pulling speed just starts to increase, due to the increase in shear force and the change in thixotropy, the material is more likely to spread on the substrate, causing the membrane thickness to decrease first. However, as the pulling speed increases further, the distribution of the material on the substrate may be affected by other factors, such as gravity, solution viscosity, etc. These factors cause the membrane thickness to begin to increase.

[0067] 5.1.3 Effect of drying temperature on proton exchange membrane thickness

[0068] Depend on Figure 3 It can be seen that with the increase of drying temperature, the thickness of the proton exchange membrane shows a trend of first decreasing and then increasing. When the drying temperature is 60°C, the minimum thickness of the proton exchange membrane is 35±1μm. This is because the increase in drying temperature will accelerate the evaporation rate of the solvent (such as water, organic solvent, etc.) in the proton exchange membrane. The rapid evaporation of the solvent will cause the volume of the membrane to shrink, which may cause a slight reduction in the membrane thickness. After the temperature is increased, the solvent on the surface of the membrane may evaporate first, forming a harder shell layer, while the internal solvent continues to evaporate and may generate internal pressure. When the internal pressure is large enough, the shell may be stretched or expanded, resulting in an increase in membrane thickness.

[0069] 5.2 Results and analysis of response surface experiment on optimization of proton exchange membrane preparation process

[0070] Design-Expert software was used to perform response surface analysis on the level of each factor. The results are shown in Table 2, and the results of the variance analysis are shown in Table 3. The quadratic regression equation was used to fit the test results in Table 3, and the regression equation was obtained using the proton exchange membrane thickness (d) as the response value: d = 35.19-0.75A-0.34B-0.11C-0.38AB+0.29AC-0.61BC+4.85A 2 +1.72B 2 +2.61C 2

[0071] Table 2 Response surface experimental design and results of pull-up coating method

[0072]

[0073]

[0074] Table 3 Analysis of variance of response surface test results of pull-up coating method

[0075]

[0076] In the variance analysis, the P value is used to explain the influence of each experimental factor on the experimental results: P<0.05 indicates that each experimental factor has a significant influence on the experimental results; P<0.01 indicates that the experimental factor has an extremely significant influence on the experimental results. According to Table 3, the F value of the response surface test result model of the film pulling process is 4.58, and the P value is 0.0286 (<0.05). The influence of the regression model is significant, so the model can be used to predict the film pulling process. The data influence results in Table 3 show that the pulling speed and drying temperature have a great influence on the film thickness of the film pulling process, among which the first-order term C is an extremely significant term (P<0.01), the first-order term B is significant (P<0.05), and the other terms have no significant effect on the film thickness. Therefore, the final optimization equation is: d=35.19-0.34B-0.11C.

[0077] Through regression equation analysis, it can be seen that the main order of factors affecting film thickness is: drying temperature > pulling speed > mass fraction, and drying temperature has a significant effect on the PEEK sulfonation process.

[0078] The response surface area plot of the Design-Expert software can be used to analyze the effect of the interaction between response variables on the response value. The response surface area plot includes a three-dimensional surface plot and a contour surface. The contour surface consists of the response value and the corresponding two interactive experimental variables. The three-dimensional surface plot shows the influence trend of each response variable and its interaction on the response value. The projection of the response surface plot is a contour plot. The flatter the curve of the three-dimensional surface plot, the flatter the ellipse in the contour plot, and the faster the color change, indicating that the interaction term has a more significant effect on the response value. The three-dimensional analysis of the interaction between experimental factors obtained using the Design-Expert software is shown in Figure 1. Figure 5-7 shown.

[0079] Depend on Figure 5-7 It can be seen that the three-dimensional surface slopes of the interaction terms AB and AC are steeper, the contour ellipses are flatter, and the color changes faster, indicating that the interactions between the mass fraction and the pulling speed, and the mass fraction and the drying temperature in the process of pulling the coating are greater than other interaction terms.

[0080] According to Design-Expert software, the optimal process conditions for pulling coating are: mass fraction 2.08%, pulling speed 82.23mm / min, and drying temperature 60.30℃. In order to verify the predictability of the model and consider the feasibility of actual operation, the process was adjusted to: mass fraction 2.1%, pulling speed 82mm / min, and drying temperature 60.3℃. The result (d=33±1μm) is similar to the optimized DS parameter content (d=33μm). Therefore, the response surface method can be used to optimize the regression model of the pulling coating process.

[0081] 5.3 Proton conductivity test

[0082] Experimental tests show that the proton conductivity of the proton exchange membrane is 729.66 mS / cm at 80°C.

[0083] Comparative example 1.

[0084] A method for preparing a PTFE membrane comprises the following steps:

[0085] A 1*2 cm polytetrafluoroethylene membrane was immersed in anhydrous ethanol, ultrasonically cleaned for 30 minutes, and then dried at 100° C. The prepared membrane was acidified in a 1 mol / L sulfuric acid solution for 24 hours, then washed with water until neutral, and dried to obtain a PTFE membrane with a thickness of about 30 μm.

[0086] Experimental tests show that polytetrafluoroethylene membrane does not directly conduct protons, and the proton conductivity is 0mS / cm.

[0087] Comparative example 2.

[0088] A method for preparing a LCSC membrane by solution casting comprises the following steps:

[0089] 0.478g of meta-aramid fiber with liquid crystal properties was slowly added to 19ml of polyetheretherketone casting solution containing sulfonic acid side chains, and stirred at 60°C for 3h to obtain sulfonated polyetheretherketone casting solution with liquid crystal properties. The solution was poured into a mold and dried at 50°C for 24h to form a membrane; the prepared membrane was acidified in a 1mol / L sulfuric acid solution for 24h, then washed with water to neutrality, and dried to obtain a LCSC proton exchange membrane, the thickness of which was about 255μm.

[0090] Experimental tests show that the proton conductivity of the proton exchange membrane is 373.3 mS / cm at 80°C.

[0091] The proton conductivity of the proton exchange membranes prepared in Example 1 and Comparative Example 2 was tested under the same environment. The results are as follows: Figure 8 As shown, from Figure 8The results show that the proton conductivity of the proton exchange membrane of Example 1 is greater than the proton conductivity of the proton exchange membrane of Comparative Example 2.

[0092] Comparative example 3.

[0093] A method for preparing a LCSC film by a film-lifting coating method comprises the following steps:

[0094] 0.478g of meta-aramid fiber with liquid crystal properties was slowly added to 19ml of polyetheretherketone casting solution containing sulfonic acid side chains, and stirred at 60°C for 3h to obtain a sulfonated polyetheretherketone casting solution with liquid crystal properties. A glass sheet was immersed in the LCSC casting solution, and then the glass sheet was pulled up to obtain a glass sheet coated with the casting solution. After drying at 50°C for 24h, no film could be formed.

Claims

1. A method for preparing a proton exchange membrane by response surface optimization, characterized in that: The specific steps include: Step 1, immersing a glass sheet with polytetrafluoroethylene as a substrate in a sulfonated polyetheretherketone casting liquid containing liquid crystal properties, and then pulling the substrate upward to obtain a substrate coated with the casting liquid; Step 2, taking the mass fraction of the casting solution, the pulling speed and the drying temperature as the influencing factors, performing multiple single factor extraction tests on the proton exchange membrane, taking the membrane thickness as the judgment standard, and obtaining the influence of each factor on the membrane thickness of the proton exchange membrane according to the single factor test; Step 3, using the response surface method to optimize the three variable parameters of the casting solution mass fraction, the pulling speed and the drying temperature, and obtaining the regression equation with the film thickness as the response value; Step 4: According to the quadratic regression model equation, the condition corresponding to the minimum value of the membrane thickness under the interaction of the factors under consideration is determined as the optimal production process parameter of the proton exchange membrane; Step 5: Prepare a proton exchange membrane according to the optimal production process parameters of step 4.

2. The method for preparing a proton exchange membrane by response surface optimization according to claim 1, characterized in that: In the step 1, the preparation method of the glass sheet with polytetrafluoroethylene as the matrix is: immersing the polytetrafluoroethylene membrane in anhydrous ethanol, ultrasonically cleaning it for 30 minutes and then drying it at 100° C. to obtain a treated PTFE membrane, and pasting the treated PTFE membrane to a clean glass sheet to obtain a glass sheet with polytetrafluoroethylene as the matrix.

3. The method for preparing a proton exchange membrane by response surface optimization according to claim 1, characterized in that: In the step 1, the method for preparing the sulfonated polyetheretherketone casting liquid containing liquid crystal properties is: the polyetheretherketone proton exchange membrane casting liquid containing sulfonic acid side chains and the meta-aramid fiber containing liquid crystal properties are mixed and stirred at 60° C. for 3 hours to obtain a casting liquid containing 1%-5% by mass of the meta-aramid fiber containing liquid crystal properties.

4. The method for preparing a proton exchange membrane by response surface optimization according to claim 1, characterized in that: In the above 2, the mass fraction of the casting liquid is 1%-5%, the pulling speed is 20-100 mm / min, and the drying temperature is 40-80°C.

5. The method for preparing a proton exchange membrane by response surface optimization according to claim 1, characterized in that: In step 3, the mass fraction of the casting solution is 1%-3%, the pulling speed is 60-100 mm / min, and the drying temperature is 50-70°C.

6. The method for preparing a proton exchange membrane by response surface optimization according to claim 1, characterized in that: In step 3, the regression equation is: d=35.19-0.75A-0.34B-0.11C-0.38AB+0.29AC-0.61BC+4.85A 2 +1.72B 2 +2.61C 2 ; In the formula, the response value d is the film thickness, unit is μm; A is the mass fraction, that is, the mass fraction of the casting liquid, unit is %; B is the pulling speed, unit is mm / min; C is the drying temperature, unit is ℃.

7. The method for preparing a proton exchange membrane by response surface optimization according to claim 1, characterized in that: In step 4, the optimal production process parameters are: the mass fraction of the casting liquid is 2.08%, the pulling speed is 82.23 mm / min, and the drying temperature is 60.30°C.

8. The method for preparing a proton exchange membrane by response surface optimization according to claim 1, characterized in that: In step 4, the minimum value of the film thickness is 33±1 μm.

Citation Information

Cited By

  • Proton exchange membrane for regulating and controlling perfluorinated sulfonic acid resin / sulfonated polyether ether ketone interface through liquid crystal ionomer grafted aramid fiber as well as preparation method and application of proton exchange membrane

    CN120545419A